2006
DOI: 10.1074/jbc.m509958200
|View full text |Cite
|
Sign up to set email alerts
|

A Structural and Functional Analysis of α-Glucan Recognition by Family 25 and 26 Carbohydrate-binding Modules Reveals a Conserved Mode of Starch Recognition

Abstract: Starch-hydrolyzing enzymes lacking ␣-glucan-specific carbohydrate-binding modules (CBMs) typically have lowered activity on granular starch relative to their counterparts with CBMs. Thus, consideration of starch recognition by CBMs is a key factor in understanding granular starch hydrolysis. To this end, we have dissected the modular structure of the maltohexaose-forming amylase from Bacillus halodurans (C-125). This five-module protein comprises an N-terminal family 13 catalytic module followed in order by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
111
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 45 publications
1
111
0
Order By: Relevance
“…These are widely used in studies of heterogeneous catalytic degradation of insoluble substrates as well as in applications taking advantage of the CBM affinity to direct enzyme-CBM fusion proteins to the surface of the substrate in question (Juge et al 2006). In addition to the first identified SBD (CBM20), 7 CBM families of SBDs have been reported (Boraston et al 2004(Boraston et al , 2006Machovic & Janecek 2006. Moreover, certain regions of the polypeptide chain in GH31 from plants were demonstrated to confer affinity for granular starch (Nakai et al 2008).…”
Section: Binding To Starchesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are widely used in studies of heterogeneous catalytic degradation of insoluble substrates as well as in applications taking advantage of the CBM affinity to direct enzyme-CBM fusion proteins to the surface of the substrate in question (Juge et al 2006). In addition to the first identified SBD (CBM20), 7 CBM families of SBDs have been reported (Boraston et al 2004(Boraston et al , 2006Machovic & Janecek 2006. Moreover, certain regions of the polypeptide chain in GH31 from plants were demonstrated to confer affinity for granular starch (Nakai et al 2008).…”
Section: Binding To Starchesmentioning
confidence: 99%
“…Some common principles may be used to describe the mechanistic action of glycoside hydrolases for degradation of recalcitrant substrates, such as cellulose, other cell wall polysaccharides, or starches (Boraston et al 2004(Boraston et al , 2006Nakai et al 2008). A variety of CBMs representing an array of polysaccharide specificities have been identified (http://www.cazy.org/).…”
Section: Binding To Starchesmentioning
confidence: 99%
“…In addition, the affinity between the enzyme and the substrate was enhanced by having tandem CBMs. 24) IGTase that has the tandem CBM25 should strongly adsorb raw starch.…”
Section: The Igtase Genementioning
confidence: 99%
“…8,9) More importantly, among CBM family 26 AmyAs, L. amylovorus AmyA and Bacillus halodurans maltohexaose forming amylase (G6 amylase) have been demonstrated to have SBDs. 10) Mizokami 2) and Satoh et al 3) reported that S. bovis 148 AmyA has an ability to adsorb onto raw starch, but they did not analyze its SBD. Few studies on bacterial amylase family s SBD have been reported, especially, expression and functional analysis of SBD itself is rare.…”
mentioning
confidence: 99%
“…Few studies on bacterial amylase family s SBD have been reported, especially, expression and functional analysis of SBD itself is rare. 10) In this study, we aim to determine the SBD of S. bovis 148 AmyA and elucidate its role in raw starch degradation.…”
mentioning
confidence: 99%